Integration of status consumption and theory of planned behavior: a conceptual framework - Altaf, Syed Naveed; Perumal, Selvan; Hussin, Zolkafli (2017)
The theory of planned behavior (TPB) is a popular theory to predict human behavior in many social science studies, consumer behaviour being no exception. The TPB in its simplest form postulates that human actions can be predicted by their intentions towards that action, and assumes that this is because humans are rational beings. Despite its popularity, TPB has been criticized in previous research on a number of grounds.TPB is essentially confined to rational behavior of humans. However, humans are not always rational in their behaviors. TPB misses out on personality, motivation, learning, lifestyles, and emotions related constructs. Thus, TPB’s utility in predicting intentions has been questioned by previous researchers. It has been empirically found to predict between 35% and 66% of the variance in intentions towards behavior. These findings indicate the presence of additional predictor constructs of purchase intentions either directly or indirectly. Furthermore, products that are perceived as status symbols do not just satisfy functional needs of the consumers but also their social and status needs. Therefore, the current study integrates status consumption with the three independent variables of TPB, namely attitudes, subjective norms, perceived behavioral control in to a single framework and proposes that addition of status consumption will increase the predictive power of TPB for products perceived as status symbols by consumers.